Associations of meditation with telomere dynamics: a case–control study in healthy adults - Dasanayaka, Nirodhi Namika; Sirisena, Nirmala Dushyanthi; Samaranayake, Nilakshi (Frontiers in Psychology, 2023)
Introduction Telomeres are protective end caps of chromosomes which naturally shorten with each cell division and thus with age. Short telomeres have been associated with many age-related diseases. Meditation has come to the fore as a mind–body practice which could influence the telomere dynamics underlying these phenomena. We previously reported meditation to be associated with higher telomerase levels, mindfulness and quality of life. Here, reporting on the same study population, we describe associations between long-term meditation and telomere length (TL), expression of hTERT and hTR genes and methylation of the promoter region of hTERT gene. Methods Thirty healthy meditators and matched non-meditators were recruited. TL was measured using quantitative PCR, gene expression was assessed using reverse transcriptase PCR, and methylation level was quantified by bisulfite-specific PCR followed by Sanger sequencing. Comparisons between meditators and controls were carried out using t-tests, while Pearson correlation was used to identify correlations, and regression was used to identify predictors. Results Males comprised 63.4% of each group with an average age of 43 years. On average, they had meditated daily for 5.82 h (±3.45) for 6.8 years (±3.27). Meditators had longer relative TLs (p = 0.020), and TL decreased with age (p < 0.001) but was not associated with other socio-demographic variables. Regression analysis showed that age (p < 0.001) and duration of meditation (p = 0.003) significantly predicted TL. The meditators showed higher relative expression of hTERT (p = 0.020) and hTR (p = 0.029) genes while the methylation level of the promoter region of hTERT gene was significantly lower when compared to non-meditators (p < 0.001). Negative correlations were identified between the methylation level of the promoter region of hTERT gene and the expression of the hTERT gene (p = 0.001) and duration of meditation (p = 0.001). Conclusion The findings suggest that meditation as a lifestyle practice has multi-level beneficial effects on telomere dynamics with potential to promote healthy aging.